2011
DOI: 10.1111/j.1574-695x.2011.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformanssuppresses the activation of bone marrow–derived dendritic cells stimulated with its own DNA, but not with DNA from other fungi

Abstract: DNA from Cryptococcus neoformans activates bone marrow-derived dendritic cells (BM-DCs) in a TLR9-dependent manner. In this study, we examined the effect of the culture supernatants of C. neoformans on the activation of BM-DCs caused by its own DNA. C. neoformans supernatants suppressed IL-12p40, IL-6 production and CD40 expression by BM-DCs stimulated with its own DNA, but not with CpG-ODN and DNA from Candida albicans, Saccharomyces cerevisiae or Escherichia coli. In a confocal microscopic analysis, C. neofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Later studies identified a specific URA5 gene fragment of cryptococcal DNA that can activate bone marrow-derived DCs (BMDCs) in a TLR9-dependent manner [ 10 ]. Additionally, although DNA of C. neoformans activates BMDCs via TLR9 [ 9 ], the culture supernatants from Cryptococcus neoformans suppress activation of BMDCs stimulated with cryptococcal DNA, but not with DNA from other fungi [ 11 ]. Mice lacking TLR9 have an increased susceptibility to C. neoformans infection, and TLR9 appears to be required for recruitment of DCs to the site of infection [ 9 , 12 , 13 ] ( Table 1 ).…”
Section: Recognition Of Cryptococcus By Dcsmentioning
confidence: 99%
“…Later studies identified a specific URA5 gene fragment of cryptococcal DNA that can activate bone marrow-derived DCs (BMDCs) in a TLR9-dependent manner [ 10 ]. Additionally, although DNA of C. neoformans activates BMDCs via TLR9 [ 9 ], the culture supernatants from Cryptococcus neoformans suppress activation of BMDCs stimulated with cryptococcal DNA, but not with DNA from other fungi [ 11 ]. Mice lacking TLR9 have an increased susceptibility to C. neoformans infection, and TLR9 appears to be required for recruitment of DCs to the site of infection [ 9 , 12 , 13 ] ( Table 1 ).…”
Section: Recognition Of Cryptococcus By Dcsmentioning
confidence: 99%
“…and several other fungi secrete polysaccharides and protein cargos through dedicated exosomes upon host interaction. Supernatant of C. neoformans cultures inhibit TLR9 activation by C. neoformans DNA (Yamamoto et al, 2011). Similarly, A. fumigatus cell wall components differentially modulate TLR2 and TLR4 signaling (Chai et al, 2011).…”
Section: Fungal Strategies To Escape or Subvert Detection By Toll-likmentioning
confidence: 99%
“…Microglial cells express Toll-like receptors (TLRs) which can identify pathogen-associated molecular patterns (PAMPs) and thereby play an important role as regulators of the innate immune response [14,15]. While bacterial lipoproteins and zymosan, a component of Saccharomyces cerevisiae ( S. cerevsiae ), are recognized by TLR2, lipopolysaccharide (LPS) from Gram-negative bacteria and glucuronoxylomannan, the major capsular polysaccharide of C. neoformans , are ligands of TLR4, and bacterial and also fungal DNA activates TLR9 [16-19]. Upon TLR stimulation, the ability of microglia to phagocytose Gram-positive and Gram-negative bacteria is increased [20,21].…”
Section: Introductionmentioning
confidence: 99%